2018
DOI: 10.1111/ctr.13217
|View full text |Cite
|
Sign up to set email alerts
|

Angioplasty vs stent in the treatment of transplant renal artery stenosis

Abstract: Stent placement resulted in fewer cases of restenosis compared with angioplasty alone, although no benefit in terms of serum creatinine, blood pressure, or patient and graft survival was shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…Another study reported a restenosis rate of 28% in patients treated with angioplasty alone and of 8% in patients treated with stenting. 29 The median follow-up period was longer in our study compared to other published studies, but the reintervention rate was concordant with the current literature. 2…”
Section: Discussionsupporting
confidence: 92%
“…Another study reported a restenosis rate of 28% in patients treated with angioplasty alone and of 8% in patients treated with stenting. 29 The median follow-up period was longer in our study compared to other published studies, but the reintervention rate was concordant with the current literature. 2…”
Section: Discussionsupporting
confidence: 92%
“…Renal artery stenosis after transplantation has been reported to be 1% to 23% in the literature, although the true incidence may vary depending on the routine screening and the method of diagnosis of the stenosis. [23,24] Graft dysfunction and hypertension are the most common indications for intervention. Treatment options include medical management, percutaneous transluminal angioplasty, stent placement and surgical reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Only 35 studies provided enough data for meta-analysis. An overall summary of the included studies, size, and evidence grading can be found in Supplemental Table S1 2,4,7,12,27-77 . We propose a diagnostic and therapeutic algorithm that reflects the findings, which is displayed in Figure 2 on the basis of the frequency of reporting cutoff parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Current studies that compared both techniques report increased baseline luminal narrowing in patients undergoing stenting, suggesting possible biases in patient selection and susceptibility. Chen et al 64 suggested defaulting to PTA in cases with <70% stenosis, whereas Macchini et al 66 used stenting after suboptimal primary PTA. Biederman 58 , however, has highlighted the benefits of stenting in restenosis rates; this finding is supported by evidence produced by this meta-analysis, showing significantly reduced restenosis when stenting is applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation